The Role of Ashura rituals and post-Ashura days in spiritual health through promoting religious-oriented normal behavior: A practical model - Mahbubeh-sadat Ebrahimnegad Shirvani; Ata Pourabbasi (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Islamic world especially Shia experience some different atmosphere in Muharram because of Ashura. This atmosphere can provide a proper field for reducing some maladaptive behaviors and stabilizing religious-based behaviors in society by setting up Ashura rituals in all cities. Surely cultural policy makers wish to remain this spiritual atmosphere for other times in order to improve spiritual health in people. Methods: In this regard, Authors try to provide some practical solutions through Ashura rituals and their analysis according to some behavioral models such as transtheoretical model of behavioral change. All ethical issues were observed. Moreover, the authors did not report conflict of interest. Results: several behavioral strategies may be offered according to time of interventions lasts from Ashura rituals. These solutions can lead to institutionalization of favorable and adaptive behaviors both in individual and social level. Conclusion: In this paper, it istried to introduce the practical solutions by reviewing the dimensions of behavior changes and matching them with the circumstances of society in Muharram. For downloading the full-text of this article please click here.